2008
DOI: 10.1007/s10620-008-0525-2
|View full text |Cite
|
Sign up to set email alerts
|

Restriction Fragment Length Polymorphism of Urease C and Urease B Genes of Helicobacter pylori Strains Isolated from Brazilian Patients with Peptic Ulcer and Chronic Gastritis

Abstract: The aim of the present work is to identify the presence of Helicobacter pylori bacterium in samples of gastric mucosa fragments, obtained by gastric biopsy, from Brazilian patients with peptic ulcer and chronic gastritis and also to determine differences among the prevalent strains in these two diseases by urease C and urease B genes amplification utilizing nested polymerase chain reaction (PCR) and PCR. We encountered 17 genotyping patterns for urease C and 7 for urease B and, although no significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The strain-specific genes found in the comparison of sequenced strains are consistent with earlier studies that demonstrated the high diversity of the H. pylori genome [4749]. Consequently, this high level of genetic diversity can be an important factor in its adaptation to the host stomach and for the clinical outcome of the infection although this aspect remains unclear.…”
Section: H Pylori Eradication and Prevention Of Gastric Cancersupporting
confidence: 87%
“…The strain-specific genes found in the comparison of sequenced strains are consistent with earlier studies that demonstrated the high diversity of the H. pylori genome [4749]. Consequently, this high level of genetic diversity can be an important factor in its adaptation to the host stomach and for the clinical outcome of the infection although this aspect remains unclear.…”
Section: H Pylori Eradication and Prevention Of Gastric Cancersupporting
confidence: 87%
“…PCR-RFLP has been frequently used for genotyping and discrimination of H. pylori strains because it is low cost, rapid, easy to perform and can be used to analyze H. pylori genotype diversity ( Röesler et al , 2009 ). The two restriction endonucleases Hha I and Mbo I were chosen for RFLP analysis of the ure C gene ( Li et al , 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…From Gastritis to Gastric Cancer: The Importance of CagPAI of Helicobacter Pylori on the Development of Early and Advanced Gastric Adenocarcinoma http://dx.doi.org/10.5772/53208 With respect specifically to the bacterium strains, H. pylori has a high level of genetic diversity that represents an important factor in its adaptation to the host stomach and also for the clinical outcome of the infection [32,33]. Virulence factors of Helicobacter pylori are essential players in modulating the immune response involved in the initiation of carcinogenesis in the stomach.…”
Section: Introductionmentioning
confidence: 99%